2016
DOI: 10.1016/j.ejc.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

An Erdős–Ko–Rado theorem for finite 2-transitive groups

Abstract: We prove an analogue of the classical Erdős-Ko-Rado theorem for intersecting sets of permutations in finite 2-transitive groups. Given a finite group G acting faithfully and 2-transitively on the set Ω, we show that an intersecting set of maximal size in G has cardinality |G|/|Ω|. This generalises and gives a unifying proof of some similar recent results in the literature.2010 Mathematics Subject Classification. Primary 05C35; Secondary 05C69, 20B05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 38 publications
(67 reference statements)
0
52
0
Order By: Relevance
“…Indeed, all our trivial examples are built from these intersecting families, which are the is indicator functions x + i . In the group case, EKR theorems are known for all 2-transitive groups, and the largest examples are indeed Boolean degree 1 functions [46], so classifying all Boolean degree 1 functions on 2-transitive groups would be very interesting. One of the classical results in analysis of Boolean functions on the hypercube, the Friedgut-Kalai-Naor theorem [31], states that a Boolean function on the hypercube which almost has degree 1 (in the sense that it is close in L 2 norm to a degree 1 function, which is not necessarily Boolean) is close to a Boolean degree 1 function.…”
Section: Future Workmentioning
confidence: 99%
“…Indeed, all our trivial examples are built from these intersecting families, which are the is indicator functions x + i . In the group case, EKR theorems are known for all 2-transitive groups, and the largest examples are indeed Boolean degree 1 functions [46], so classifying all Boolean degree 1 functions on 2-transitive groups would be very interesting. One of the classical results in analysis of Boolean functions on the hypercube, the Friedgut-Kalai-Naor theorem [31], states that a Boolean function on the hypercube which almost has degree 1 (in the sense that it is close in L 2 norm to a degree 1 function, which is not necessarily Boolean) is close to a Boolean degree 1 function.…”
Section: Future Workmentioning
confidence: 99%
“…The group PSU(3, q) has a twotransitive action on a set of size q 3 + 1, we will only consider this action. In [17] it is shown that PSU (3, q) has the EKR property, here we give more details of this result and further give a result about the largest intersecting sets in PSU (3, q). Namely, we prove that the characteristic vector for any maximum intersecting set in PSU(3, q) is a linear combination of characteristic vectors of the canonical cliques in PSU (3, q).…”
Section: Introductionmentioning
confidence: 85%
“…Equality holds since any canonical set meets this bound. This means that the group PSU(3, q) has the EKR property (this is shown in [17]). By Tables 3 and 4, provided that q = 5, only χ 2 gives the eigenvalue that gives equality in the equation for Hoffman's bound.…”
Section: Character Numbermentioning
confidence: 97%
See 2 more Smart Citations